Perovskite-ion beam interactions : toward controllable light emission and lasing - Wang, Yue (2020)
Achieving controllable coherent and incoherent light sources is crucial to meet the requests of the constantly developing integrated optics, which, however, remains challenging for the existing semiconductor materials and techniques. All-inorganic lead halide perovskites (ILHPs) are emerging as the promising semiconductors, featuring the defect-tolerant nature and tunable band gap. Herein, an experimental design, based on the interaction between ILHPs and energetic ions, for achieving controllable light emitters and microlasers is reported. We reveal that the photoluminescence intensity from ILHPs can be modulated by more than 1 order of magnitude upon low-dose gallium ion (∼1015 ions/cm2) irradiation, which can be attributed to the generation of vacancy/interstitial defects, metallic lead, and crystal-to-amorphization transition. Such ion-dependent light emission can be exploited to make the colorful photopatterns and in situ tailor the lasing behavior from CsPbBr3 microplates. Further, a strong sputtering effect is observed with the increase of the ion dose (∼1017 ions/cm2), which enables the top-down fabrication of microlasers based on ILHPs. These findings represent a significant step toward controllable light sources leveraging on perovskite-ion interactions.